2014
DOI: 10.1080/09168451.2014.925782
|View full text |Cite
|
Sign up to set email alerts
|

A short-term ingestion of fructo-oligosaccharides increases immunoglobulin A and mucin concentrations in the rat cecum, but the effects are attenuated with the prolonged ingestion

Abstract: We examined the effects of fructo-oligosaccharides (FOS) on IgA and mucin secretion in the rat cecum after different ingestion periods. Rats were fed a control diet or a diet containing FOS for 1, 2, 4, and 8 wk. FOS ingestion greatly increased IgA and mucin concentrations at 1 and 2 wk, but the effects were disappeared or attenuated at 4 and 8 wk. After 1 wk, FOS induced higher lactobacilli and lactate concentrations and lower cecal pH in the cecum, but the alterations were moderated with the prolonged ingest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…In accordance with our previous studies (11,31), FOS supplementation induced a very acidic fermentation in the cecum due to the accumulation of lactate and succinate in rats fed SP for 9 d. FOS ingestion was also accompanied by simultaneous significant increases in gut permeability (as assessed by urinary Cr-EDTA excretion and translocation of bacteria into MLNs) and myeloperoxidase activities (as a marker of neutrophil accumulation), and the expressions of inflammatory cytokine genes in the cecal tissues. In contrast, the fermentation pattern in rats fed NP was characterized by the production toward more SCFA and less succinate and lactate, irrespective of supplemental FOS in the diet.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with our previous studies (11,31), FOS supplementation induced a very acidic fermentation in the cecum due to the accumulation of lactate and succinate in rats fed SP for 9 d. FOS ingestion was also accompanied by simultaneous significant increases in gut permeability (as assessed by urinary Cr-EDTA excretion and translocation of bacteria into MLNs) and myeloperoxidase activities (as a marker of neutrophil accumulation), and the expressions of inflammatory cytokine genes in the cecal tissues. In contrast, the fermentation pattern in rats fed NP was characterized by the production toward more SCFA and less succinate and lactate, irrespective of supplemental FOS in the diet.…”
Section: Discussionsupporting
confidence: 91%
“…Mucinase activity was analyzed as described previously [79]. Briefly, fecal samples were mixed with acetate buffer (pH 5.5) at a ratio of 1:400 (w/v) and used for the mucinase assay with porcine stomach mucin as a substrate, according to a previously described method [80].…”
Section: Mucinase Activity Analysismentioning
confidence: 99%
“…In addition, newer research has indicated that butyrate regulates gut mucosal homeostasis and elicits modulatory effects on dendritic cells [ 61 ] and on the differentiation of colonic regulatory T cell [ 62 , 63 , 64 ]. A new study in rats also showed that a short term (1 week and 2 weeks) ingestion of FOS significantly increased IgA and mucin concentrations in cecum, but this effect was attenuated with a prolonged ingestion [ 65 ], indicating development of a state of tolerance due to long exposure of this dietary treatment. Indeed, most of the studies dealing with immune-stimulating effects of iS ingestion are done in short-term studies.…”
Section: Prebiotic Properties Of Is and Effects Of Fermentationmentioning
confidence: 99%